Performance investigation on a novel liquid desiccant regeneration system operating in vacuum condition - Yon, Hao Ren (2020)
Liquid Desiccant Dehumidification Systems (LDDS) have been gaining attention due to its great energy saving potential in buildings. The desiccant regeneration system in LDDS plays a vital role in the system as the major energy consumed is due to the heat energy supplied to regain the concentration of the desiccant solution. The high regeneration temperature prohibits the potential use of low-grade or renewable energy as the heat source in the desiccant regeneration system. Therefore, a desiccant regeneration system operating in vacuum condition was proposed in this work. A novel Absorption-based Liquid Desiccant Regeneration (ALDR) system was developed and studied to validate this approach. A performance prediction model was also developed to predict the regeneration performance of the ALDR system. The model predicted values and the experimental values agreed well with each other with average deviation less than 5.90%. The operating parameters in the proposed ALDR system were also compared with the conventional packed-bed desiccant regeneration system available in literature. The regeneration temperature in LDDS was found to be significantly reduced to around 20–35 °C with the operating vacuum pressure between 1000 Pa and 2000 Pa when regenerating Lithium Bromide solution of 36% mass fraction. This study validated the feasibility of the ALDR system in reducing the regeneration temperature of the desiccant regeneration system. The results also showed that the proposed ALDR system was able to reduce the power consumption by 40.66% compared to the conventional packed-type regenerator from literature.